Improving uptake of hepatitis B and hepatitis C testing in South Asian migrants in community and faith settings using educational interventions—A prospective descriptive study. (November 2020) - Kelly, Claire; Pericleous, Marinos; Ahmed, Ayesha; Vandrevala, Tushna; Hendy, Jane; Shafi, Shuja; Skene, Simon S.; Verma, Sumita; Edge, Chantal; Nicholls, Margot; Gore, Charles; de Lusignan, Simon; et al.
Highlights: Emphasis both nationally and internationally has switched to case-finding and subsequent linkage to care for hepatitis B and C, in accordance with the World Health Organization call for the elimination of chronic viral hepatitis (CVH) by 2030. This entails evolving roles for clinicians, who are taking on more of this case-finding role, which has traditionally fallen to UK public health. We describe the results of our study on an educational intervention (a short film) designed to encourage South Asian migrants to test for CVH. Culturally relevant interventions including faith and culturally sensitive settings appear to minimize logistical issues and effectively engage minority groups, allowing ease of access to individuals 'at risk', including older members and women. Abstract: Background: Chronic viral hepatitis (CVH) is a leading contributor to the UK liver disease epidemic, with global migration from high prevalence areas (e.g., South Asia). Despite international guidance for testing high-risk groups in line with elimination targets, there is no consensus on how to achieve this. The objectives of this study were to assess the following: (1) the feasibility of recruiting South Asian migrants to view an educational film on CVH, (2) the effectiveness of the film in promoting testing and increasing knowledge of CVH, and (3) the methodological issues relevant to scale-up to a randomized controlled trial. Methods: South Asian migrants were recruited to view the film (intervention) in community venues (primary care, religious, community), with dried blood spot CVH testing offered immediately afterwards. Pre/post-film questionnaires assessed the effectiveness of the intervention. Results: Two hundred and nineteen first-generation migrants ≥18 years of age (53% female) were recruited to view the film at the following sites: religious, n = 112 (51%), community n = 98 (45%), and primary care, n = 9 (4%). One hundred and eighty-four (84%) underwent CVH testing; hepatitis B core antibody or hepatitis C antibody positivity demonstrated exposure in 8.5%. Pre-intervention ( n = 173, 79%) and post-intervention ( n = 154, 70%) questionnaires were completed. Conclusions: This study demonstrated the feasibility of recruiting first-generation migrants to view a community-based educational film promoting CVH testing in this higher risk group, confirming the value of developing interventions to facilitate the global World Health Organization plan for targeted case finding and elimination, and a future randomized controlled trial. We highlight the importance of culturally relevant interventions including faith and culturally sensitive settings, which appear to minimize logistical issues and effectively engage minority groups, allowing ease of access to individuals 'at risk'.